Influence of Motivation and Job Training The Performance of Employees PT. RB Sukasada Palembang. - Ika Rakhmalina; Emelda Emelda; Harapin Hafid; Periansya Periansya (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
The purpose of this study was to determine the effect of motivation and job training to employees performance of PT. RB Sukasada. This research is causality. The population in this study is the overall employees of PT. RB Sukasada Jl. Kebumen Land No. 901-902, 17 Ilir, Ilir Tim. I, Palembang, South Sumatra 30122, amounting to 39 employees, with census sampling.Data collection techniques used in this study was a questionnaire with the answer given a score based on a scale interval of 1-5 with the Likert method. With multiple linear regress analysis tools. The next test of the hypothesis that f test and t-test to determine of independent variables on the dependent variable, and making inferences. Data analysis techniques in this study assisted by the Statistical program for special science (SPSS) The results of research by F test resulted in no significant effect Motivation and Job Training together with the Employee Performance at PT. RB Sukasada with a coefficient of determination (R Square) of 34.9%. While based on the t-test a significant difference between motivation and job training partially on performance. With the results of multiple regression 57.0% effect of motivation on the performance and 47.6% influence on the performance of job training. Conclusion motivation and job training are still low in achieving performance.